2012
DOI: 10.2478/v10173-012-0019-7
|View full text |Cite
|
Sign up to set email alerts
|

Influence of working fluid evaporation temperature in the near-critical point region on the effectiveness of ORC power plant operation

Abstract: In the paper presented are definitions of specific indicators of power which characterize the operation of the organic Rankine cycle (ORC) plant. These quantities have been presented as function of evaporation temperature for selected working fluids of ORC installation. In the paper presented also is the procedure for selection of working fluid with the view of obtaining maximum power. In the procedure of selection of working fluid the mentioned above indicators are of primary importance. In order to obtain ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
3
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 1 publication
2
3
0
Order By: Relevance
“…In addition, an interesting conclusion was reached by the authors [35] who found that in certain variants of the power plant, where the fluid is evapo- rated in near-critical conditions the capacities achieved may be higher than in the use of supercritical cycle. Similar conclusions, however, for the subcritical cycle are given in [36]. The authors [36] highlight the advantages of the use of the evaporation agent in the near-subcritical conditions and the impact of evaporator work parameters on the efficiency of the ORC power plant.…”
Section: Supercritical Orc Power Plants Powered By the Energy From Bi...supporting
confidence: 52%
See 1 more Smart Citation
“…In addition, an interesting conclusion was reached by the authors [35] who found that in certain variants of the power plant, where the fluid is evapo- rated in near-critical conditions the capacities achieved may be higher than in the use of supercritical cycle. Similar conclusions, however, for the subcritical cycle are given in [36]. The authors [36] highlight the advantages of the use of the evaporation agent in the near-subcritical conditions and the impact of evaporator work parameters on the efficiency of the ORC power plant.…”
Section: Supercritical Orc Power Plants Powered By the Energy From Bi...supporting
confidence: 52%
“…Similar conclusions, however, for the subcritical cycle are given in [36]. The authors [36] highlight the advantages of the use of the evaporation agent in the near-subcritical conditions and the impact of evaporator work parameters on the efficiency of the ORC power plant.…”
Section: Supercritical Orc Power Plants Powered By the Energy From Bi...supporting
confidence: 52%
“…Work analysis of ORC systems is the subject of many papers. These analyses concern many aspects, including: the selection of suitable evaporation temperature, type of working fluid [1,2] or ORC systems connectivity with other energy systems [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…The results indicated that the evaporator's internal and external entropy generation was the main source of total entropy generation, and the maximum cycle efficiency of the testing system is 5.2%. With the deepening of the study, the singular properties of organic fluids in near-critical region and the near-critical cycle walk gradually into researchers' vision [7][8][9][10][11][12]. With an eye to the large drastically of fluid thermo physical and transport properties in near-critical region, Trela [10] proposed a method for determination of the near-critical region that is based on variations of specific heat capacity along isobars.…”
Section: Introductionmentioning
confidence: 99%